2003
DOI: 10.1046/j.1537-2995.2003.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

RBC alloimmunization and autoimmunization among transfusion‐dependent Arab thalassemia patients

Abstract: Several factors might have contributed to the high alloimmunization and autoimmunization rate observed in this study, including the heterogeneity of the population living in Kuwait, lack of better-matched donors for those patients, and the use of poststorage leukodepleted blood. It is recommended that thalassemia patients receive blood matched for Rh and Kell antigens and prestorage leukodepleted RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
144
6
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(173 citation statements)
references
References 32 publications
(40 reference statements)
15
144
6
1
Order By: Relevance
“…As seen the reported alloimmunisation rates in thalassemics from other parts of India vary from 3.79-9.48 % [8,13,19]. In our study frequency of alloimmunization and autoimmunization was 8.6 and 1.8 % respectively which is similar to that reported from other centers in our country.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As seen the reported alloimmunisation rates in thalassemics from other parts of India vary from 3.79-9.48 % [8,13,19]. In our study frequency of alloimmunization and autoimmunization was 8.6 and 1.8 % respectively which is similar to that reported from other centers in our country.…”
Section: Discussionsupporting
confidence: 88%
“…Their data was similar to an Asian study which reported autoantibodies in 25 % of their thalassaemia patients [5]. Also a study from Kuwait observed autoantibodies in 11 % of their patients [19]. However, a study in Iran found autoantibodies in 1.4 % of their thalassemia patients [9].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations